KRITIK MUSṬAFA A’ẒAMĪ TERHADAP PANDANGAN ORIENTALIS TENTANG HADIS NABI - Kurnaini, Mohammad; Muhammad Wahid Abdullah (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
The defense of the Prophet's ḥadīth ﷺ has been carried out by Muslim scholars throughout the ages. In earlier times, they examined the chains of transmission (sanad) and compiled ḥadīth into collections. However, with the emergence of Orientalist scholars, Muslim scholars began to critique Orientalist views on ḥadīth. Orientalists argued that ḥadīth were not the sayings of the Prophet ﷺ, but rather statements of later Muslim scholars, with isnāds retroactively constructed to trace back to the Prophet ﷺ. Among the theories proposed by Orientalists to critique the sanad are Projecting Back, Argumentum e Silentio, and Common Link. Meanwhile, they questioned the authenticity of ḥadīth texts (matn) by linking them to the political context of the time. This study uses a qualitative method with a library research approach. One of the Muslim scholars who significantly contributed to refuting these Orientalist views is Muḥammad Muṣṭafā al-Aʿẓamī. Through his dissertation, he effectively exposed the weaknesses in the Orientalists' theories, showing that their conclusions were inconsistent with historical facts due to the incompleteness of their data.